2012
DOI: 10.1111/j.1744-9987.2012.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Interleukin‐10 by Combining a Granulocyte and Monocyte Adsorption Carrier With Ulinastatin

Abstract: Interleukin (IL)-10 is an anti-inflammatory cytokine mainly produced by monocytes and is essential for the induction of anti-inflammatory intestinal macrophages with macrophage colony-stimulating factor (M-CSF). Thus, IL-10- and M-CSF-rich conditions in colonic tissues seem to contribute to the improvement of pathological conditions in patients with inflammatory bowel diseases (IBD). We have already reported that ulinastatin, a serine protease inhibitor, increases M-CSF production during granulocyte/monocyte (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Therefore, the reduction of TGF‐β release via CA beads might be due to this reduction of Th17‐cell differentiation, which may be one of the mechanisms of clinical efficacy of GMA in patients with IBD. Moreover, we also revealed that ulinastatin not only had the ability to increase the release of anti‐inflammatory cytokines, such as IL‐1ra and IL‐10 , but that it could also decrease TGF‐β release (Fig. ) in combination with GM and platelet adsorption to CA beads.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Therefore, the reduction of TGF‐β release via CA beads might be due to this reduction of Th17‐cell differentiation, which may be one of the mechanisms of clinical efficacy of GMA in patients with IBD. Moreover, we also revealed that ulinastatin not only had the ability to increase the release of anti‐inflammatory cytokines, such as IL‐1ra and IL‐10 , but that it could also decrease TGF‐β release (Fig. ) in combination with GM and platelet adsorption to CA beads.…”
Section: Discussionmentioning
confidence: 70%
“…We have already reported that cytokine release (e.g. IL‐1ra, HGF, IL‐10, and TNF‐α) is augmented by GM adsorption to CA beads . Thus, we expected that TGF‐β release would be augmented by incubation with CA beads because platelets, which produce TGF‐β, are also adsorbed (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…We previously reported that contact between peripheral blood and cellulose acetate (CA) beads used as carriers for granulocyte and monocyte (GM) adsorptive apheresis (GMA) increases plasma HGF concentration (3), through unknown signaling pathways that are involved in HGF production in GM adsorption to CA beads. On the other hand, we also reported that ulinastatin, a serine protease inhibitor, increased the production of anti-inflammatory cytokines such as interleukin (IL)-1 receptor antagonist and IL-10 in combination with GM adsorption to CA beads (4). In this study, we investigated the effect of ulinastatin on HGF production in GM adsorption and elucidate the signaling pathway involved.…”
mentioning
confidence: 99%